As obras francesas da Coleção Yêdda e Augusto Frederico Schmidt: sistematização, avaliação e divulgação - Vicente, Adalberto Luis [UNESP]; Vivaldini, Raissa Daniela [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The project aims to provide information on the French works of Yêdda and Augusto Frederico Schmidt Collection to the academic community and the general public, encouraging its use by the community, both the general reader, as the critical reader or researcher. As a first project facing the Collection, the aim is also to stimulate new research in it. In addition, the project aims to undergraduates and graduate students interested in learning more about the Collection or conduct research in various fields of the humanities to explore its rich content . Anyway is expected to give dynamism to the Collection, from the idea that a Collection of this nature and importance must be "alive", to interact significantly and steadily with the community, providing a source of new knowledge, research and stimulating reading.

O projeto pretende oferecer informações sobre as obras francesas da Coleção Yêdda e Augusto Frederico Schmidt, incentivando o uso do acervo, tanto pelo leitor comum, quanto pelo leitor crítico ou pesquisador. Como primeiro projeto voltado para a referida Coleção, pretende-se também incentivar novas pesquisas no acervo. Além disso, o projeto pretende que alunos de graduação e pós-graduação interessados em conhecer melhor o acervo ou desenvolver pesquisa em áreas diversas das ciências humanas possam explorar seu rico conteúdo. Enfim, esperase dar dinamismo à Coleção, a partir da concepção de que um acervo desta natureza e importância deve ser “vivo”, no sentido de interagir de modo significativo e constante com a comunidade, tanto interna quanto externa à universidade, fornecendo-lhe uma fonte de novos conhecimentos, de pesquisa e de estímulo à leitura.
Keywords: Reading; French works; Yêdda and Augusto Frederico Schmidt Collection; Leitura; Obras francesas; Coleção Yêdda e Augusto Frederico Schmidt